Congress's Telangana victory: import of the Karnataka model - Zarhani, Seyed Hossein; Mukherji, Rahul (The wire, 2024)
The Congress's Telangana victory is the result of a well-executed strategy encompassing strong leadership, welfare-oriented policies, secularism and civil society support, all within the challenging environment of competitive authoritarianism.